Czy szkoła trwa niezmiennie, czy niezmieniona? Egalitaryzm i elitaryzm w podejściu do edukacji w dobie: globalizacji, technopolizacji, kultury instant - Przybyła, Mariusz (Studia Edukacyjne, 2018)
Globalisation and new media have completely changed the living environment of modern humanity. Technologies have entered almost all spheres of human existence. Education also could not (should not) remain unchanged. The presence of electronic media in the educational process forces a thinking pedagogue to ask questions, including the following: Who are the digital natives and the digital immigrants? Is the contemporary school on the verge of a chance that it has not had so far? Is this an opportunity to enrich and develop human cognitive function, using the available technical means, by deliberately influencing the course of a number of human life processes, including our development?